BIOMASS AND CHLOROPHYLL ANALYSIS OF Ceriops tagal IN DIFFERENT NURSERY MEDIA - Herna Maghfira Raudhatul Jannah; Erwin Riyanto Ardli; Elly Proklamasiningsih (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Ceriops tagal is a major mangrove species that plays an important role in the mangrove ecosystem. Ceriops tagal is one type of mangrove that has benefits for various marine organisms such as fish, shrimp, nematodes, etc also can maintain the stability of the mangrove ecosystem. In rehabilitation, it is necessary to have a nursery. The addition of husk and husk charcoal to the nursery media can increase the absorption space for water, air, and plant nutrients. The research aims to (1) determine the effect of differences in nursery media with a mixture of husk and husk charcoal on mud media; (2) determine which nursery media has the best effect on biomass and chlorophyll content of C. tagal mangroves. This research started from planting the propagules of C. tagal in different composition growing media with husk and husk charcoal then calculated with ANOVA test 5% and 1% of the biomass in root, stem, leaves, and hypocotyl also chlorophyll content in leaves of C. tagal organ. Then proceed with the honest significant difference test 5% for the wet biomass of root, dry biomass of stem, root, and wet also dry biomass hypocotyl of C. tagal. Research obtained that modification of nursery media with husk and husk charcoal can increase dry biomass of root and stem also wet and dry biomass of hypocotyl in C. tagal organs. The media best media for increase the biomass of the C. tagal in each organ was media 5 (composed of mud + husk charcoal in ratio 2:1) and media 6 (composed of mud + husk + husk charcoal in ratio 1:1:1). The increasing dry biomass of root and stem also wet and dry biomass of hypocotyl are also affected by environmental factors such as pH content in the medium.